The Exploration of Religious Moderation Discourse as a New Form of Nationalism in the Indonesian Government - Syahbudi (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2025)
On September 22, 2021, Cinta Laura delivered a commencement speech at the Launching Night for Religious Moderation Action held by the Ministry of Religious Affairs. Cinta Laura is known as a young female artist and grew up in an environment of Western education. Her attendance conveys a significant message about what and who the main target of the religious moderation policy is. This article employed a critical discourse analysis method to examine religious moderation through the lens of the hegemonic state policy. Secondary data are obtained from books, articles, opinions, and news in both print and electronic mass media that explain the concepts and ideas of religious moderation, especially since 2020. The question is, how is the policy of religious moderation constructed today? What is the purpose of the policy? The article argues that the state promotes religious moderation to strengthen the legitimacy of the new nationalism. This policy aims to nationalize religious views to influence how people view the relationship between religion and the state. It is accomplished, in part, by implementing policies that promote the debunking of narratives of religious intolerance, especially in educational institutions. Additionally, the state promotes socio-cultural norms that are perceived as beneficial to the state in terms of maintaining stability. The critical contribution of this article is that, through religious moderation policies, the state has managed to mitigate the political impact of intolerance; however, this approach tends to be formalistic and ceremonial.